Determinants of migrants remittances in Malaysia: an ARDL approach - Elijah, Sunday; Hamzah, Hanny Zurina; Hook, Law Siong; Kaliappan, Shivee Ranjanee (Iran University of Science and Technology, 2024)
This article analyses what determines remittance inflows into Malaysia. Using the Autoregressive distributed lag (ARDL) approach, the study used time-series data for the period 1987-2018. The study validated the theory that remittance inflows ought to be encouraged through determinants such as real wages, inflation, financial development, exchange rate among others. Variables like exchange rate, inflation, gross domestic product growth, financial development and real wages significantly determine the remittance received into Malaysia. Precisely, inflation and real wages significantly impacted and positively encouraged remittance inflows into Malaysia from abroad. On the other hand, remittance inflows reacted negatively to gross domestic products growth, exchange rate and financial development. Furthermore, the significance of the determinants differs. Precisely, real wages happen to be additionally responsive in comparison to inflation and the reason is that its elasticity is greater. In addition, both inflation and real wages have a great impact in Malaysia. This study recommends that the determinants of migrants' remittances in the country should be given attention which will strongly aid in employing remittances for the reduction of poverty, rising investment at the national level and therefore, aid in boosting growth and enhancing sustainable development to Malaysia.